Institutional Ownership Memoderasi Pengaruh Komite Keberlanjutan, Jenis Industri Dan Penghargaan Terhadap Sustainability Reporting - Tabita Novikurniasari Harijanto; Nofryanti Nofryanti; Iin Rosini (Politeknik Ganesha Medan, 2026)
This study aims to analyze the influence of sustainability committees, industry types, and awards on sustainability reporting, and to examine the role of institutional ownership moderation in non-financial companies listed on the Indonesia Stock Exchange (IDX). The sample consists of 224 companies from 11 major sectors based on the IDX-IC classification, with active criteria registered by the end of 2024 and publishing identifiable sustainability reporting. The analysis method used multiple linear regression and Moderated Regression Analysis (MRA). The results showed that sustainability and awards committees had a positive, significant influence on sustainability reporting, whereas industry type did not. In addition, institutional ownership does not significantly moderate the relationship between sustainability committees, industry types and rewards for sustainability reporting. These findings suggest that institutional investors have not used sectoral characteristics or sustainability awards to assess the strength of a company's ESG signals, thereby failing to strengthen sustainability reporting practices. Theoretically, the study broadens the understanding of the application of signal theory in developing countries, while practically providing implications for management, regulators, and investors to strengthen sustainability governance, drive ESG transparency, and balance financial orientation with long-term sustainability commitments.